2022
DOI: 10.3390/molecules27175496
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Photocatalytic Oxidation of Methane to Methanol

Abstract: Methane is one of the promising alternatives to non-renewable petroleum resources since it can be transformed into added-value hydrocarbon feedstocks through suitable reactions. The conversion of methane to methanol with a higher chemical value has recently attracted much attention. The selective oxidation of methane to methanol is often considered a “holy grail” reaction in catalysis. However, methanol production through the thermal catalytic process is thermodynamically and economically unfavorable due to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 127 publications
0
15
0
Order By: Relevance
“…CH 4 is one of the prospective substitutes for non-renewable petroleum resources since it can be converted to other added value-chemicals, such as syngas for NH 3 production and CH 3 OH. 48 Currently, CH 3 OH is produced using a thermal catalytic process in which syngas is produced (H 2 and CO) from steam reforming of CH 4 at high process conditions (very high temperature and pressure), and then hydrogenated to produce CH 3 OH. Photocatalytic partial oxidation of CH 4 is an alternative way of producing CH 3 OH at ambient temperatures and potentially using solar light; reducing the energy requirements means reducing the greenhouse gas emissions released to the atmosphere.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…CH 4 is one of the prospective substitutes for non-renewable petroleum resources since it can be converted to other added value-chemicals, such as syngas for NH 3 production and CH 3 OH. 48 Currently, CH 3 OH is produced using a thermal catalytic process in which syngas is produced (H 2 and CO) from steam reforming of CH 4 at high process conditions (very high temperature and pressure), and then hydrogenated to produce CH 3 OH. Photocatalytic partial oxidation of CH 4 is an alternative way of producing CH 3 OH at ambient temperatures and potentially using solar light; reducing the energy requirements means reducing the greenhouse gas emissions released to the atmosphere.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…74–76 A few review papers have been recently published on photo-partial oxidation of CH 4 , and we invite the reader to consult them for a deeper knowledge of the topic. 48,77,78 CH 4 + ˙OH → ˙CH 3 + H 2 O…”
Section: Green Fuelsmentioning
confidence: 99%
“…25 In particular, heterojunction systems have been attempted as an effective strategy for enhancing the overall photocatalytic efficiency of TiO 2 -based photocatalysts. 26 For heterojunctions, the incorporation of alternative semiconductors such as WO 3 may synergistically improve the photocatalytic efficiency of TiO 2 under visible light irradiation, resulting from optical and electronic property modification. 27,28 Additionally, the use of various co-catalysts is proven to be an effective approach to augment charge carrier separation.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the reaction is catalyzed by a [Cu−O−Cu] 2+ motif formed via a hypothesized proton‐assisted diffusion of hydrated Cu ions in the cages of SSZ‐13 zeolites [4] . Recently, photocatalytic oxidation of methane to methanol has been intensively discussed based on materials and engineering perspectives [24] . However, so far it has not been possible to develop a catalyst that would give satisfactory reaction results.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, photocatalytic oxidation of methane to methanol has been intensively discussed based on materials and engineering perspectives. [24] However, so far it has not been possible to develop a catalyst that would give satisfactory reaction results. As it has been shown in the literature, reasonable methanol yields with high selectivity have still not been achieved.…”
Section: Introductionmentioning
confidence: 99%